Integration of Madrasah diniyah learning systems for strengthening religious moderation in Indonesian universities - Ngainun Naim; Abdul Aziz; Teguh Teguh (Institute of Advanced Engineering and Science, 2022)
Madrasah diniyah is a very special Islamic education system in Indonesia that can be implemented from primary, secondary, and even higher education levels. This study aimed to explain the integration of the madrasah system in Islamic Religious Universities in the framework of strengthening religious moderation. The research method used was qualitative with a symbolic interactionalism approach. The main informants in this study were eleven people from the elements of the chancellor, vice-rector 1, head of Madrasah diniyah (Mudhir), teachers/ustadz, and students at State Islamic Institute (IAIN) Tulungagung selected by purposive sampling technique. The research implementation procedure was technically carried out by the stages of data collection, reduction, presentation, and analysis. This study found that the integration of the Madrasah diniyah system into the learning system at IAIN Tulungagung is quite effective in increasing students' religious knowledge. The implementation of Madrasah diniyah needs the support of all stakeholders in higher education. The obstacles faced need to be minimized in terms of infrastructure improvement and participant readiness. The Madrasah diniyah system which is integrated into the learning system in universities is a breakthrough in the world of higher education. With the effective integration of the Madrasah diniyah system into the learning system at Islamic religious universities, the implementation of Madrasah diniyah requires the support of all stakeholders. Therefore, the Madrasah diniyah system integration model is a model that can be developed in other Islamic religious universities.